Transgender from a religious perspective and its implications in personality education - Wahyono Wahyono; Husnul Khotimah; Nelly Husni Laely (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2026)
This study examines transgender phenomena from religious and psychological perspectives and identifies their implications for personality education. The study retains the author's original analytical direction by comparing Sigmund Freud's structure of personality with Al-Ghazali's conception of desire, reason, and the heart. To ensure methodological consistency with the available evidence, the research is designed as qualitative library research using thematic content analysis and comparative-conceptual analysis. Twenty-one core sources were purposively selected from peer-reviewed articles, scholarly books, Islamic legal and ethical documents, and authoritative health-classification and educational sources. The analysis proceeded through source identification, data reduction, thematic coding, comparative mapping, and interpretive synthesis. The findings show, first, that transgender identity must be distinguished from sexual orientation, gender expression, and clinically significant distress. Second, the literature does not support a single causal explanation; biological, developmental, family, social, cognitive, and cultural factors interact in different ways. Third, Freud and Al-Ghazali both describe personality as a dynamic relation among impulses, regulatory capacities, and moral orientation, although their philosophical foundations and goals are different. Fourth, neither framework is sufficient to conclude that all transgender individuals are dominated by the pleasure principle or uncontrolled desire. Rather, both theories can be used cautiously to analyze tensions among identity, desire, social expectations, religious values, and self-regulation. The study contributes a religiously grounded and psychologically informed framework for personality education based on conceptual accuracy, moral reflection, self-control, empathetic dialogue, family involvement, protection from humiliation and violence, and referral to competent counseling when distress is present. The main limitation is that the study is theoretical and does not represent the direct experiences of transgender participants.